Microwave-assisted extraction, HPLC analysis, and inhibitory effects on carbonic anhydrase I, II, VA, and VII isoforms of 14 blueberry Italian cultivars. (4th November 2016) - Mollica, Adriano; Locatelli, Marcello; Macedonio, Giorgia; Carradori, Simone; Sobolev, Anatoly P.; De Salvador, Roberto F.; Monti, Simona M.; Buonanno, Martina; Zengin, Gokhan; Angeli, Andrea; Supuran, Claudiu T.
Abstract: The multi-component fingerprint and the biological evaluation of plant-derived material are indispensable for the pharmaceutical field, in food quality control procedures, and in all plant-based products. We investigated the quantitative content of biologically active compounds (anthocyanins and chlorogenic acid) of microwave-assisted blueberry extracts from 14 different Italian cultivars, using validated high-performance liquid chromatography-photodiode array detector (HPLC-PDA) method and routinely instrument configuration. The carbonic anhydrase (CA, EC 4.2.1.1) inhibition profiles against several pharmacologically relevant CA isoforms of blueberry extracts and some bioactive compounds were also investigated. The various cultivars showed a highly variable content in anthocyanins and chlorogenic acid, and their CA inhibitory effects were also highly variable. Overall these data prove that antioxidant natural products found in blueberries may be useful for designing pharmacological agents in which various CAs are involved, e.g., antiobesity, antitumor, or anticonvulsants agents.